2014
DOI: 10.1002/jcph.263
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of dabrafenib, a BRAF inhibitor: Effect of dose, time, covariates, and relationship with its metabolites

Abstract: Dabrafenib is a BRAF kinase inhibitor indicated for the treatment of BRAF V600E mutation-positive melanoma. The population pharmacokinetics of dabrafenib, including changes over time and relevant covariates, were characterized based on results from four clinical studies using a nonlinear mixed effects model with a full covariate approach. Steady-state exposures of dabrafenib metabolites (hydroxy-, carboxy-, and desmethyl-dabrafenib) were characterized separately. The pharmacokinetics of dabrafenib were adequat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 20 publications
7
61
0
Order By: Relevance
“…It was observed that plasma AUC0‐12 h (day 21) of dabrafenib at repeat dosing was lower than that at AUC0‐inf (day 1), which may support the result that dabrafenib induces self‐induction of metabolism. The results observed in this study are consistent with the results that have been observed in global studies 28. Similarly rapid absorption of trametinib was also noticed following repeated dosing of trametinib 2 mg q.d.…”
Section: Discussionsupporting
confidence: 92%
“…It was observed that plasma AUC0‐12 h (day 21) of dabrafenib at repeat dosing was lower than that at AUC0‐inf (day 1), which may support the result that dabrafenib induces self‐induction of metabolism. The results observed in this study are consistent with the results that have been observed in global studies 28. Similarly rapid absorption of trametinib was also noticed following repeated dosing of trametinib 2 mg q.d.…”
Section: Discussionsupporting
confidence: 92%
“…The proportion of patients reaching their predefined efficacy target was comparable between both age groups, with 68% of elderly patients and 61% of younger patients reaching the target ( P = 0.17), as shown in Table . Although no clinically relevant target concentration has been established for dabrafenib, a pooled population PK analysis of four clinical trials reported a typical pre‐dose concentration of 46.6 ng ml −1 . This plasma concentration was reached by 94% of older patients and 74% of younger patients, not reaching significance ( P = 0.11).…”
Section: Resultsmentioning
confidence: 98%
“…As both alectinib and M4 inhibit ALK with similar potency in vitro and exhibit similar plasma protein binding, it is believed that both alectinib and M4 contribute to overall alectinib efficacy and safety, and thus the effect of posaconazole on the combined exposure of alectinib and M4, adjusted for molecular weight, was determined. This approach has been applied to interpretation of clinical data for other tyrosine kinase inhibitors with active metabolites (eg, regorafenib, dabrafenib, and sunitinib) . Coadministration with posaconazole only had a minor effect on the combined exposure of alectinib and M4, with a geometric mean ratio for AUC 0–∞ of 136%.…”
Section: Discussionmentioning
confidence: 99%